Cost-benefit analysis of mitigating subsidence damage in Semarang and Demak, Indonesia - Pratiwi, Berlian A.; Kok, Sien; Kaiser, Brooks Alexandra; Mahya, Muthia J. (Frontiers in Environmental Economics, 2023)
Since the early 1990s, the coastal Semarang City in Indonesia has been undergoing rapid industrialization and population expansion. To meet growing water demand, groundwater is abstracted with an ever-increasing number of abstraction wells. This has led to lower groundwater tables in the largely unconsolidated substrate and this, in turn, causes land subsidence in the area. This has led to significant direct and indirect economic damage. In the context of limited public resources, this study aims to analyze the economic rationale of alternative (public) investment strategies to reduce subsidence impact in the Semarang-Demak region. With Cost-Benefit Analysis (CBA), three alternative strategies to replace groundwater abstraction wells are analyzed: (1) Installment of a piped clean water supply system with 1,000 L/s capacity, (2) a new 2 km2 coastal freshwater reservoir in West Semarang, (3) installment of a piped clean water supply system with 2,000 L/s capacity. All strategies have a positive (>1) benefit-cost ratio, which indicates that there is an economic rationale for investment to mitigate subsidence in Semarang and Demak. Under a low water demand scenario, the best strategy is strategy 1; under a high water demand scenario, the best strategy is strategy 3. As strategy 3 gives the highest economic benefit in the worst-case scenario, this is the most robust strategy.